Recent advances in copper-catalyzed asymmetric coupling reactions - Zhou, Fengtao; Cai, Qian (Beilstein Journal of Organic Chemistry, 2015)
Copper-catalyzed (or -mediated) asymmetric coupling reactions have received significant attention over the past few years. Especially the coupling reactions of aryl or alkyl halides with nucleophiles became a very powerful tool for the formation of C–C, C–N, C–O and other carbon–heteroatom bonds as well as for the construction of heteroatom-containing ring systems. This review summarizes the recent progress in copper-catalyzed asymmetric coupling reactions for the formation of C–C and carbon–heteroatom bonds.
Keywords: asymmetric; carbon–heteroatom bond; copper; coupling

(untitled) - Ullmann, F.; Bielecki, J. (Ber. Dtsch. Chem. Ges., 1901)

(untitled) - Ullmann, F. (Ber. Dtsch. Chem. Ges., 1903)

(untitled) - Goldberg, I. (Ber. Dtsch. Chem. Ges., 1906)

(untitled) - Ullmann, F.; Sponagel, P. (Ber. Dtsch. Chem. Ges., 1905)

(untitled) - Hurtley, W. R. H. (J. Chem. Soc., 1929)

(untitled) - Ley, S. V.; Thomas, A. W. (Angew. Chem., Int. Ed., 2003)

(untitled) - Kunz, K.; Scholz, U.; Ganzer, D. (Synlett, 2003)

(untitled) - Beletskaya, I. P.; Cheprakov, A. V. (Coord. Chem. Rev., 2004)

(untitled) - Evano, G.; Blanchard, N.; Toumi, M. (Chem. Rev., 2008)

(untitled) - Monnier, F.; Taillefer, M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Ma, D.; Cai, Q. (Acc. Chem. Res., 2008)

(untitled) - Sambiagio, C.; Marsden, S. P.; Blacker, A. J.; McGowan, P. C. (Chem. Soc. Rev., 2014)

(untitled) - Cai, Q.; Zhou, F. (Synlett, 2013)

(untitled) - Hassan, J.; Sévignon, M.; Gozzi, C.; Schulz, E.; Lemaire, M. (Chem. Rev., 2002)

(untitled) - Miyano, S.; Tobita, M.; Suzuki, S.; Nishikawa, Y.; Hashimoto, H. (Chem. Lett., 1980)

(untitled) - Miyano, S.; Tobita, M.; Hashimoto, H. (Bull. Chem. Soc. Jpn., 1981)

(untitled) - Miyano, S.; Handa, S.; Shimizu, K.; Tagami, K.; Hashimoto, H. (Bull. Chem. Soc. Jpn., 1984)

(untitled) - Miyano, S.; Handa, S.; Tobita, M.; Hashimoto, H. (Bull. Chem. Soc. Jpn., 1986)

(untitled) - Miyano, S.; Fukushima, H.; Handa, S.; Ito, H.; Hashimoto, H. (Bull. Chem. Soc. Jpn., 1988)

(untitled) - Dai, D.; Martin, O. R. (J. Org. Chem., 1998)

(untitled) - Gorobets, E.; McDonald, R.; Keay, B. A. (Org. Lett., 2006)

(untitled) - Stavrakov, G.; Keller, M.; Breit, B. (Eur. J. Org. Chem., 2007)

(untitled) - Nelson, T. D.; Meyers, A. I. (Tetrahedron Lett., 1994)

(untitled) - Nelson, T. D.; Meyers, A. I. (Tetrahedron Lett., 1993)

(untitled) - Nelson, T. D.; Meyers, A. I. (J. Org. Chem., 1994)

(untitled) - Meyers, A. I.; Willemsen, J. J. (Chem. Commun., 1997)

(untitled) - Degnan, A. P.; Meyers, A. I. (J. Am. Chem. Soc., 1999)

(untitled) - Lin, G.-Q.; Zhong, M. (Tetrahedron Lett., 1996)

(untitled) - Tanaka, K.; Suzuki, H.; Osuga, H. (J. Org. Chem., 1997)

(untitled) - Lipshutz, B. H.; Kayser, F.; Liu, Z.-P. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Sugimura, T.; Yamada, H.; Inoue, S.; Tai, A. (Tetrahedron: Asymmetry, 1997)

(untitled) - Spring, D. R.; Krishnan, S.; Schreiber, S. L. (J. Am. Chem. Soc., 2000)

(untitled) - Andrus, M. B.; Asgari, D.; Sclafani, J. A. (J. Org. Chem., 1997)

(untitled) - Lin, G.-Q.; Zhong, M. (Tetrahedron: Asymmetry, 1997)

(untitled) - Coleman, R. S.; Grant, E. B. (J. Am. Chem. Soc., 1995)

(untitled) - Michaud, G.; Bulliard, M.; Ricard, L.; Genêt, J.-P.; Marinetti, A. (Chem. – Eur. J., 2002)

(untitled) - Madec, J.; Michaud, G.; Genêt, J.-P.; Marinetti, A. (Tetrahedron: Asymmetry, 2004)

(untitled) - Qiu, L.; Wu, J.; Chan, S.; Au-Yeung, T. T.-L.; Ji, J.-X.; Guo, R.; Pai, C.-C.; Zhou, Z.; Li, X.; Fan, Q.-H.; Chan, A. S. C. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Xie, X.; Chen, Y.; Ma, D. (J. Am. Chem. Soc., 2006)

(untitled) - Takenaka, K.; Itoh, N.; Sasai, H. (Org. Lett., 2009)

(untitled) - Porosa, L.; Viirre, R. D. (Tetrahedron Lett., 2009)

(untitled) - Rossen, K.; Pye, P. J.; Maliakal, A.; Volante, R. P. (J. Org. Chem., 1997)

(untitled) - Tagashira, J.; Imao, D.; Yamamoto, T.; Ohta, T.; Furukawa, I.; Ito, Y. (Tetrahedron: Asymmetry, 2005)

(untitled) - Kreis, M.; Friedmann, C. J.; Bräse, S. (Chem. – Eur. J., 2005)

(untitled) - Zhou, F.; Guo, J.; Liu, J.; Ding, K.; Yu, S.; Cai, Q. (J. Am. Chem. Soc., 2012)

(untitled) - Zhou, F.; Cheng, G.-J.; Yang, W.; Long, Y.; Zhang, S.; Wu, Y.-D.; Zhang, X.; Cai, Q. (Angew. Chem., Int. Ed., 2014)

(untitled) - Liu, J.; Yan, J.; Qin, D.; Cai, Q. (Synthesis, 2014)

(untitled) - He, N.; Huo, Y.; Liu, J.; Huang, Y.; Zhang, S.; Cai, Q. (Org. Lett., 2015)

(untitled) - Liu, J.; Tian, Y.; Shi, J.; Zhang, S.; Cai, Q. (Angew. Chem., Int. Ed., 2015)

(untitled) - Yang, W.; Long, Y.; Zhang, S.; Zeng, Y.; Cai, Q. (Org. Lett., 2013)

(untitled) - Long, Y.; Shi, J.; Liang, H.; Zeng, Y.; Cai, Q. (Synthesis, 2015)

(untitled) - Quamar Salih, M.; Beaudry, C. M. (Org. Lett., 2013)

(untitled) - Yang, W.; Yan, J.; Long, Y.; Zhang, S.; Liu, J.; Zeng, Y.; Cai, Q. (Org. Lett., 2013)

(untitled) - Shi, J.; Wang, T.; Huang, Y.; Zhang, X.; Wu, Y.-D.; Cai, Q. (Org. Lett., 2015)

(untitled) - Yang, W.; Liu, Y.; Zhang, S.; Cai, Q. (Angew. Chem., Int. Ed., 2015)

(untitled) - Hoveyda, A. H.; Hird, A. W.; Kacprzynski, M. A. (Chem. Commun., 2004)

(untitled) - Yorimitsu, H.; Oshima, K. (Angew. Chem., Int. Ed., 2005)

(untitled) - Falciola, C. A.; Alexakis, A. (Eur. J. Org. Chem., 2008)

(untitled) - Harutyunyan, S. R.; den Hartog, T.; Geurts, K.; Minnaard, A. J.; Feringa, B. L. (Chem. Rev., 2008)

(untitled) - Alexakis, A.; Bäckvall, J. E.; Krause, N.; Pàmies, O.; Diéguez, M. (Chem. Rev., 2008)

(untitled) - van Klaveren, M.; Persson, E. S. M.; del Villar, A.; Grove, D. M.; Bäckvall, J.-E.; van Koten, G. (Tetrahedron Lett., 1995)

(untitled) - Karlström, A. S. E.; Huerta, F. F.; Meuzelaar, G. J.; Bäckvall, J.-E. (Synlett, 2001)

(untitled) - Miyaura, N.; Suzuki, A. (Chem. Rev., 1995)

(untitled) - Shintani, R.; Takatsu, K.; Takeda, M.; Hayashi, T. (Angew. Chem., Int. Ed., 2011)

(untitled) - Takeda, M.; Takatsu, K.; Shintani, R.; Hayashi, T. (J. Org. Chem., 2014)

(untitled) - Jung, B.; Hoveyda, A. H. (J. Am. Chem. Soc., 2012)

(untitled) - Gao, F.; Carr, J. L.; Hoveyda, A. H. (Angew. Chem., Int. Ed., 2012)

(untitled) - Shido, Y.; Yoshida, M.; Tanabe, M.; Ohmiya, H.; Sawamura, M. (J. Am. Chem. Soc., 2012)

(untitled) - Hojoh, K.; Shido, Y.; Ohmiya, H.; Sawamura, M. (Angew. Chem., Int. Ed., 2014)

(untitled) - Hojoh, K.; Shido, Y.; Nagao, K.; Mori, S.; Ohmiya, H.; Sawamura, M. (Tetrahedron, 2015)

(untitled) - Yanagisawa, A.; Nomura, N.; Yamamoto, H. (Tetrahedron, 1994)

(untitled) - Matsubara, R.; Jamison, T. F. (J. Am. Chem. Soc., 2010)

(untitled) - Nakamura, H.; Bao, M.; Yamamoto, Y. (Angew. Chem., Int. Ed., 2001)

(untitled) - Zhang, P.; Brozek, L. A.; Morken, J. P. (J. Am. Chem. Soc., 2010)

(untitled) - Hornillos, V.; Pérez, M.; Fañanás-Mastral, M.; Feringa, B. L. (J. Am. Chem. Soc., 2013)

(untitled) - Fleming, I.; Barbero, A.; Walter, D. (Chem. Rev., 1997)

(untitled) - Delvos, L. B.; Vyas, D. J.; Oestreich, M. (Angew. Chem., Int. Ed., 2013)

(untitled) - Takeda, M.; Shintani, R.; Hayashi, T. (J. Org. Chem., 2013)

(untitled) - Ito, H.; Kawakami, C.; Sawamura, M. (J. Am. Chem. Soc., 2005)

(untitled) - Ito, H.; Ito, S.; Sasaki, Y.; Matsuura, K.; Sawamura, M. (J. Am. Chem. Soc., 2007)

(untitled) - Park, J. K.; Lackey, H. H.; Ondrusek, B. A.; McQuade, D. T. (J. Am. Chem. Soc., 2011)

(untitled) - Dabrowski, J. A.; Gao, F.; Hoveyda, A. H. (J. Am. Chem. Soc., 2011)

(untitled) - Harada, A.; Makida, Y.; Sato, T.; Ohmiya, H.; Sawamura, M. (J. Am. Chem. Soc., 2014)